CLASSICAL CAESAREAN SECTION WITH MYOMECTOMY- A CASE REPORT - Ishika Chakarvarti; Shraddha Shetty; Preethi K (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
: Leiomyomas are the most common benign tumors of the reproductive tract in women of childbearing age. Large fibroid present in lower uterine segment may obstruct the passage of the fetus, and in such cases, classical Caesarean delivery is indicated. Myomectomy during Caesarean section is avoided due to increased vascularity of the gravid uterus which may increase the chance of postpartum hemorrhage. However, obstetricians are opting for myomectomy along with Caesarean section to avoid complications from second surgery. Case presentation: Describing the case of 34-year G2P1L0 at 39 weeks period of gestation with previous Intra uterine death (IUD) with ultrasound showing fibroid of 9 cm in anterior lower uterine segment who underwent elective classical Caesarean section along with myomectomy. Conclusion: Myomectomy during Caesarean section can be performed safely without increase in the peripartum maternal morbidities.